Sexual and Gender Minority Victimization: Base Rates of Assault in College Students Across Sexual and Gender Identities. Issue 7 (April 2023) - Borgogna, Nicholas C.; Lathan, Emma C.; Aita, Stephen L.
Past findings have indicated that sexual and gender minority (SGM) individuals experience disproportionate rates of emotional, physical, and sexual assault compared to their heterosexual/cisgender counterparts. While these findings are robust, many studies report homogenous groupings of SGM participants. This practice likely masks important between-group differences. We sought to address this issue by examining reported base rates of emotional, physical, and sexual assault within 12 months of data collection, split across specific sexual (heterosexual, gay/lesbian, bisexual, questioning, queer, pansexual, asexual, and demisexual) and gender (cisgender men, cisgender women, gender nonconforming female assigned at birth [FAB], and gender nonconforming male assigned at birth) identity groups. Our data came from 2020 to 2021 Healthy Minds Study, a large survey of college students living in the United States ( N  = 119, 181). Results indicated most forms of assault were higher in SGM groups compared to heterosexual and cisgender individuals, both on univariate and multivariate (e.g., one or more type of assault) levels. Demisexual individuals reported the highest base rates for emotional assault (45.7%), whereas pansexual individuals reported highest rates of physical assault (12.5%) and sexual assault (17.3%). Demisexual individuals reported the highest multivariate base rate of experiencing at least one form of assault (49.5%), and pansexual individuals reported the highest multivariate base rate of experiencing all three forms of assault (4.7%) within the past 12 months. Gender nonconforming FAB individuals reported the highest univariate and multivariate base rates across assault types compared to all other gender identity groups. With few exceptions, compared to heterosexual and cisgender men (referents), all other sexual and gender identity groups reported significantly higher adjusted odds of experiencing each assault type. These data suggest SGM individuals experience disproportionate levels of assault.